Letter of the Editor - Herrera, Rafael (Cuban Journal of Agricultural Science, 2016)
From November 16th to 20th, 2015, the 5th International Congress of Tropical Animal Production was held in the Palacio de Convenciones de La Habana, Cuba, within the context of the celebrations for the 50th anniversary of the creation of the Institute of Animal Science.